Desain and Build a Medium Voltage Cubicles Temperature and Humidity Optimization Tool to Minimize the Occurrence of Corona Disease with the PLC-Based Fuzzy Method - Sheila, Sindy Yurisma; Rochamwati, Nur Wakhidatur; Riyadi, Faris; As’ad, Reza Fardiyan; Nugraha , Anggara Trisna (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2022)
Cubicle is an electrical device that functions as a breaker, protector, connector, controller, and divides the electric power system from an electric power source and reduces sparks when connecting. One of the problems that occur in medium voltage cubicles is the presence of corona. Corona phenomena at cubicle terminations can trigger disturbances such as a decrease in insulation quality, power loss and a significant increase in harmonic distortion. In this study, raised a problem regarding the optimization of temperature and humidity in cubicles using the fuzzy method to stabilize the performance of medium voltage cells. The purpose of this research is to control the temperature and humidity in the medium voltage cubicle so that it is optimal so as to minimize the occurrence of corona discharge. In addition, in this study there is a fuzzy method for controlling the fan and has been equipped with SCADA for monitoring and controlling the center of several parameters such as temperature, humidity, voltage, current and power. In this study, it was found that the fuzzy method in this prototype was able to stabilize the panel humidity at 55% RH and stabilize the panel room temperature at 31.5oC. Thus, it is hoped that a stable and optimal temperature and humidity can minimize the occurrence of corona. The use of HMI/SCADA based applications can facilitate the ability of the user (operator) to monitor several available parameters and manually control the operation of the panel (on/off).